Mixed-Mode Universal Filter Using Differential Difference Transconductance Amplifiers - Suksaibul, Pichai; Torteanchai, Usa; Kumngern, Montree; Jongchanachavawat, Wirote; Burapattanasiri, Bancha; Lerkvaranyu, Somkiat (My University, 2022)
This paper presents a new mixed-mode universal biquad filter based on differential difference transconductance amplifiers (DDTAs). This work will be expressed that many filtering functions with electronic control of the natural frequency can be obtained using DDTA-based circuit. The topology provides voltage-mode (VM), current-mode (CM), transimpedance-mode (TIM), transadmittance-mode (TAM) transfer functions into single topology and each transfer function offers five standard filtering functions. The performance of the proposed topology is carried out using PSPICE simulators based on 0.18 μm CMOS technology from TSMC. The simulation result shows that it can confirm the proposed topology.
Keywords: DDTA; differential difference transconductance amplifier; mixed-mode filter; universal filter